2021
DOI: 10.1002/nbm.4485
|View full text |Cite
|
Sign up to set email alerts
|

Quartile histogram assessment of glioma malignancy using high b‐value diffusion MRI with a continuous‐time random‐walk model

Abstract: The purpose of this study is to investigate the feasibility of using a continuous‐time random‐walk (CTRW) diffusion model, together with a quartile histogram analysis, for assessing glioma malignancy by probing tissue heterogeneity as well as cellularity. In this prospective study, 91 patients (40 females, 51 males) with histopathologically proven gliomas underwent MRI at 3 T. The cohort included 42 grade II (GrII), 19 grade III (GrIII) and 29 grade IV (GrIV) gliomas. Echo‐planar diffusion‐weighted imaging was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…M.M. [ 26 ] found that the CTRW diffusion model offers potential for exploring tumor structural heterogeneity at a subvoxel level and assessing glioma malignancy. The SM was used to monitor the treatment response (e.g., to explore the possibility of assessing early response to chemotherapy in patients with colorectal liver metastasis) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…M.M. [ 26 ] found that the CTRW diffusion model offers potential for exploring tumor structural heterogeneity at a subvoxel level and assessing glioma malignancy. The SM was used to monitor the treatment response (e.g., to explore the possibility of assessing early response to chemotherapy in patients with colorectal liver metastasis) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CTRW model naturally takes tissue cellularity and heterogeneity into its parameters (D, α, β). 17,18,20,27 The complementary nature of these three tissue properties provides the basis for combining the CTRW parameters to characterize molecular subtypes, as shown in this study.…”
Section: Discussionmentioning
confidence: 94%
“…where S 0 and S are the signal intensity in the voxel with b values of 0 and 800 mm 2 /sec, respectively. The CTRW model was calculated through the following fitting formula 17,20 :…”
Section: Quantitative Measurements Of Ctrw-dwimentioning
confidence: 99%
See 2 more Smart Citations